Wasaṭiyyah dalam Pemikiran Tafsīr Maqāṣidī Yūsuf al-Qaraḍāwī: Studi Kasus Pluralisme Agama (Journal of Comparative Study of Religions, 2023)
Tafsīr maqāsidī appears as a response to the phenomenon of partial understanding of the religious text. The mainstreaming of that exegesis is hence deemed an intellectual project aiming to translate the wasaṭiyyah into Islamic teachings. Yūsuf al-Qaraḍāwī, given his position as the main promotor of wasaṭiyyah and maqāṣid employment in religious understanding, is worth exploring. The article, therefore, aims to explore the dimension of wasaṭiyyah in al-Qaraḍāwī’s thought of tafsīr maqāsidī with special reference to religious pluralism. The data of this qualitative research is mostly taken from the works of al-Qaraḍāwī while its analysis employs two methods; content and descriptive. The article concluded that wasaṭiyyah in Yūsuf al-Qaraḍāwī’s thought of tafsīr maqasīdī lies in the balance between maqāṣid kulliyyāt which is tawhīd and nuṣūṣ juz’iyyāt which is the religious singular impression as in al-Baqarah 62. The importance of that balancing lies in the attempt to realize the Qur’an’s comprehensiveness. For, if the verse is only perceived within the literal perspective of tawhīd, it seems to neglect the wording literally promising salvation for other people of religion regardless of time boundaries. Otherwise, if the verse is meant within the religious singular paradigm, namely the salvation for people other than Muslims as long as they observe submission, such an understanding will contradict the universality of Islam itself.